The European Landscape Convention of the Council of Europe and the Landscape Award of the Council of Europe - Déjeant-Pons, Maguelonne (4D Tájépítészeti és Kertművészeti Folyóirat, 2019)
European Landscape Convention of the Council of Europe (ETS No. 176) was opened for signature by European States in Florence on 20 October 2000. To date, 39 Council of Europe member States have ratified the Convention. The Convention addressesthe Organisation’s major challenges in the field of human rights, democracy and the rule of law with a view to sustainable development.